DESIGN OF BAJAKAH ROOT CHOPPING MACHINE INTO TEA POWDER - Abdi, Muhammad Zainul; Saparin, Saparin; Setiawan, Yudi; Wijianti, Eka Sari (Politeknik Negeri Sriwijaya, Indonesia, 2023)
Tea (camellia sinensis) is one type of plant that is often found as a processed beverage. There are several raw materials for making tea that are often used including using leaves, shoots, flowers, and roots. One of the teas made from roots is bajakah root tea where the manufacturing process is still done in the traditional way, namely chopped using a machete. Therefore, in this study, a bajakah root chopping machine was designed with the aim of helping the bajakah root production process into tea powder. This bajakah root chopping machine into tea powder is designed using the France method with the demands of a sturdy frame and easy to move. This bajakah root chopping machine has dimensions of 340 mm long, 240 mm wide and 600 mm high. The engine is driven by an electric motor with a power of 0.5 Hp, a rotation of 1400 rpm using a pulley drive system with a ratio of 1: 1.5 and the rotation of the chopper shaft is 933 rpm. From the test results taken from a sample of 500 grams of raw material with 3 times testing, the resulting average is perfectly chopped as much as 389 grams, not perfectly chopped as much as 54 grams, with a time of 167.3 seconds. The production capacity of the machine is 8.37 kg/hour.Â The machine that has been made is able to chop bajakah roots with a machine production efficiency of 77.8%.